Effect of cold plasma on carotenoid content and instrumental color of carrot juice: a systematic review and meta-analysis - AMORIM, Danyelly Silva; AMORIM, Isabelly Silva; CHISTÉ, Renan Campos; FERNANDES, Fabiano André Narciso; ZANATTA, Fabrício Batistin; GODOY, Helena Teixeira; TEIXEIRA FILHO, José (Food Science and Technology, 2024)
The effect of cold plasma on carotenoid content and the instrumental color of carrot juice were evaluated. The meta-analyzed data of carrot juice showed that cold plasma resulted in a significantly higher level (95% confidence interval) in a standardized mean difference (SMD) of 4.45 for total carotenoids, for lycopene an SMD of 3.63, for ꞵ-carotene an SMD of 0.86, and for lutein an SMD of 0.55, compared with the control. After the extraction of carotenoids from the carrot juice, the highest levels were observed for the following combinations of plasma treatment versus time: total carotenoids and lutein—80 Kv/4 min; ꞵ-carotene—70 Kv/3 min; and lycopene—60 Kv/4 min. The instrumental color showed no significant differences between the plasma treatment and control for the coordinates L*, a*, and b*. Therefore, the cold plasma treatment showed a positive effect on the maintenance of carotenoids in carrot juice.